Awareness and management of chronic disease, insurance status, and health professional shortage areas in the REasons for Geographic And Racial Differences in Stroke (REGARDS): a cross-sectional study - Durant Raegan W; Parmar Gaurav; Shuaib Faisal; Le Anh; Brown Todd M; Roth David L; Hovater Martha; Halanych Jewell H; Shikany James M; Prineas Ronald J; Samdarshi Tandaw J; Safford Monika M (BMC, 2012)
Abstract Background Limited financial and geographic access to primary care can adversely influence chronic disease outcomes. We examined variation in awareness, treatment, and control of hypertension, diabetes, and hyperlipidemia according to both geographic and financial access to care. Methods We analyzed data on 17,458 participants in the REasons for Geographic And Racial Differences in Stroke (REGARDS) study with either hypertension, hyperlipidemia, or diabetes and living in either complete Health Professional Shortage Area (HPSA) counties or non-HPSA counties in the U.S. All analyses were stratified by insurance status and adjusted for sociodemographics and health behaviors. Results 2,261 residents lived in HPSA counties and 15,197 in non-HPSA counties. Among the uninsured, HPSA residents had higher awareness of both hypertension (adjusted OR 2.30, 95% CI 1.08, 4.89) and hyperlipidemia (adjusted OR 1.50, 95% CI 1.01, 2.22) compared to non-HPSA residents. Also among the uninsured, HPSA residents with hypertension had lower blood pressure control (adjusted OR 0.45, 95% CI 0.29, 0.71) compared with non-HPSA residents. Similar differences in awareness and control according to HPSA residence were absent among the insured. Conclusions Despite similar or higher awareness of some chronic diseases, uninsured HPSA residents may achieve control of hypertension at lower rates compared to uninsured non-HPSA residents. Federal allocations in HPSAs should target improved quality of care as well as increasing the number of available physicians.